Factors Modulating Post-Activation Potentiation of Jump, Sprint, Throw, and Upper-Body Ballistic Performances: A Systematic Review with Meta-Analysis - Seitz, Laurent B.; Haff, G. Gregory (Sports medicine (Auckland), 2016)
Background Although post-activation potentiation (PAP) has been extensively examined following the completion of a conditioning activity (CA), the precise effects on subsequent jump, sprint, throw, and upper-body ballistic performances and the factors modulating these effects have yet to be determined. Moreover, weaker and stronger individuals seem to exhibit different PAP responses; however, how they respond to the different components of a strength–power–potentiation complex remains to be elucidated. Objectives This meta-analysis determined (1) the effect of performing a CA on subsequent jump, sprint, throw, and upper-body ballistic performances; (2) the influence of different types of CA, squat depths during the CA, rest intervals, volumes of CA, and loads during the CA on PAP; and (3) how individuals of different strength levels respond to these various strength–power–potentiation complex components. Methods A computerized search was conducted in ADONIS, ERIC, SPORTDiscus, EBSCOhost, Google Scholar, MEDLINE, and PubMed databases up to March 2015. The analysis comprised 47 studies and 135 groups of participants for a total of 1954 participants. Results The PAP effect is small for jump (effect size [ES] = 0.29), throw (ES = 0.26), and upper-body ballistic (ES = 0.23) performance activities, and moderate for sprint (ES = 0.51) performance activity. A larger PAP effect is observed among stronger individuals and those with more experience in resistance training. Plyometric (ES = 0.47) CAs induce a slightly larger PAP effect than traditional high-intensity (ES = 0.41), traditional moderate-intensity (ES = 0.19), and maximal isometric (ES = –0.09) CAs, and a greater effect after shallower (ES = 0.58) versus deeper (ES = 0.25) squat CAs, longer (ES = 0.44 and 0.49) versus shorter (ES = 0.17) recovery intervals, multiple- (ES = 0.69) versus single- (ES = 0.24) set CAs, and repetition maximum (RM) (ES = 0.51) versus sub-maximal (ES = 0.34) loads during the CA. It is noteworthy that a greater PAP effect can be realized earlier after a plyometric CA than with traditional high- and moderate-intensity CAs. Additionally, shorter recovery intervals, single-set CAs, and RM CAs are more effective at inducing PAP in stronger individuals, while weaker individuals respond better to longer recovery intervals, multiple-set CAs, and sub-maximal CAs. Finally, both weaker and stronger individuals express greater PAP after shallower squat CAs. Conclusions Performing a CA elicits small PAP effects for jump, throw, and upper-body ballistic performance activities, and a moderate effect for sprint performance activity. The level of potentiation is dependent on the individual’s level of strength and resistance training experience, the type of CA, the depth of the squat when this exercise is employed to elicit PAP, the rest period between the CA and subsequent performance, the number of set(s) of the CA, and the type of load used during the CA. Finally, some components of the strength–power–potentiation complex modulate the PAP response of weaker and stronger individuals in a different way.